(untitled) (Gestão & Regionalidade, 2025)
This study aimed to identify and analyze the presence of research practice as a teaching and learning strategy in the Undergraduate Administration course based on a bibliographical survey carried out in the proceedings of the National Meeting of the National Association of Postgraduate Studies and Research in Administration (EnANPAD), from 2001 to 2021. Methodologically, the research was outlined through a bibliographic survey of articles published in the annals of this scientific event in the thematic area EPQ - Teaching and Research in Administration and Accounting with a focus on the first. In the period investigated, a total of 1,586 were identified in the EPQ subdivision of EnANPAD, but, of this total, only 22 are inherent to the research object and are distributed in the area of ​​Applied Social Sciences. When the analysis focuses only on the undergraduate Administration course, it appears that only five publications focus on research as a teaching and learning strategy. It is concluded that these results reveal, on the one hand, the relevance of the study, considering that the theme is little explored in the scope of academic-scientific research, and, on the other, that the use of research practice as a research procedure Teaching and learning in Undergraduate Administration courses is still a practice little used in classes by teachers.